Development of a low-cost food scrap and grease separator - Lee, Zhen Sheng (2023)
The purpose of this project is to develop a low-cost food scrap and grease separator, a device that separates food scrap and grease from the leftover food and also the food preparation process. It is to prevent the presence of food scraps, fats, oil, and grease in the drain which can cause clogging which can lead to flooding. One of the main reasons that caused floods hit Malaysia in many places in the year 2021 is the clogged drainage system. To be low cost, a simple design is selected. However, it is important to mention that simple design does not mean only the most basic functions should be retained. Features that have the potential to increase the willingness of target groups to adopt the product is also important and should be considered to add to the product. Hence, the detachable baffles are the feature that was added to the prototype. Through experiments and testing conducted, the results obtained have met the expectation, which is no oil droplets were observed from the discharged flow collected, and most of the oil separated remained in two different sections of the grease separator. Hence, the feature added does not reduce the effectiveness of the prototype but provides convenience in the more thorough discharge of oil and the cleaning process. Thence, it is believed that the added feature would increase the willingness of target groups to adopt this product. Lastly, the total cost of material used to fabricate the prototype is RM 420.27.